FRI0278 Increased risk of acute and chronic renal comorbidity in ankylosing spondylitis: Results from a population-based study. (23rd January 2014) - Levy, A.R.; Szabo, S.; Rao, S.R.; Cifaldi, M.; Maksymowych, W.P.
Abstract : Background: Clinical evidence points to an increased risk of renal comorbidity in ankylosing spondylitis (AS) compared to the general population. However, there are no population-based estimates available in the literature. An increased risk of renal comorbidity would have substantial implications for the monitoring and treatment of AS because the mainstay of pharmacological treatment is the use of non-steroidal anti-inflammatory agents (NSAIDs). Objectives: To estimate the prevalence and age- and sex-standardized increased risk of renal comorbidity, including acute and chronic kidney disease, and amyloidosis in a population-based cohort of persons diagnosed with AS in Québec between 1996 and 2006, compared to the general population. Methods: A retrospective cohort study was conducted using the administrative physician-billing database of the Régie de l'Assurance Maladie du Québec. The cohort included individuals with at least one International Classification of Diseases, 9th Revision (ICD-9) billing code for AS between 1996 and 2006. A comparison cohort was generated using a 1% random sample of individuals without AS. Renal complications were identified by ICD-9 codes for amyloidosis, hypertensive chronic renal disease, acute and chronic renal disease. Age- and sex-stratified prevalence, and standardized prevalence ratios with 95% confidence intervals (CI), of renal complications in AS compared with the general population were calculated. Sensitivity analysis was conducted using two ICD-9 codes for AS. Results: There were 8, 616 individuals identified with AS; 56% were male and the median age at diagnosis was 42 years. Overall, renal complications were diagnosed among 3.4% and 2.1% of males and females with AS, compared to 2.0% and 1.6% of males and females in the general population cohort, respectively. Prevalence of renal complications increased with age in both the AS and general population cohort. Age- and sex-stratified prevalence ratios, comparing the risk of renal complications among those with AS to the general population, demonstrated a significantly excess risk of renal complications that was highest among younger individuals with AS. Overall, individuals with AS were at a significantly increased risk of renal complications compared to members of the general population (irrespective of a coding for hypertension), with a standardized prevalence ratio of 1.7 (1.5-2.0). Standardized prevalence ratios were 6.0 (2.0-18.0) for amyloidosis; 1.7 (1.4-2.0) for chronic kidney disease; 3.2 (0.8 – 12.4) for hypertensive kidney disease, and 1.9 (1.5 – 2.3) for acute kidney disease. The excess risk was highest among younger individuals with AS, and results were similar when two ICD codes were used to identify AS. Conclusions: This population-based analysis shows that individuals with AS are at increased risk of many types of renal complications, with the excess risk being greatest among younger individuals. These data highlight the importance of careful monitoring for renal complications among those with AS, particularly during long-term continuous use of NSAIDs. Disclosure of Interest: None Declared